Instructional Design and Models: ASSURE and Kemp - Bajracharya, Jiwak Raj (Journal of Education and Research, 2019)
Instructional Design (ID) is a procedure for developing an educational or training programme, curricula, or courses sequentially and authentically (Branch & Merrill, 2011). This procedure enables instructors to create instructions, which involves the “systematic planning of instruction” (Smith & Ragan, 2005, p. 8), ranging from instructional analysis to evaluation (Mager, 1984). Thus, ID can be referred to as a “systematic and reflective process of translating principles of learning and instruction into plans for instructional materials, activities, information resources, and evaluation” (Smith & Ragan, 2005, p. 4). As such, taken as a framework, ID provides the process to create instructions based on the necessity of a teaching and learning environment. Thus, ID can be defined as a process to develop directions and specifications using learning and instructional theory to ensure the quality of instruction.